Papers devoted to the 80th jubilee of Vladilen Letokhov : Spectroscopic study of GdVO4 : Yb + Er crystals. (13th March 2020) - Klimin, S A; Loiseau, P; Caurant, D; Popova, M N
Abstract: GdVO4 crystals doped with different erbium and ytterbium concentrations have been grown in order to study their spectroscopic and kinetic properties and identify the nature of active centres in them. Their polarised transmission and luminescence spectra have been used to construct energy level diagrams of the Er 3+ ion. The lifetime of the lower level of the 4 I11/2 excited-state multiplet has been shown to decrease markedly with increasing ytterbium concentration. Inequivalent erbium centres have been observed to form in the crystals with increasing ytterbium concentration.